Importance of Definitions in the Teaching and Learning of Mathematics: Examining the Case of Linear Algebra - Chaudhary, Shankar (Adhyayan Journal, 2025)
This study explores the role of definitions in teaching and learning linear algebra, emphasizing their impact on understanding and problem-solving. By analyzing existing research, the paper highlights how precise mathematical definitions aid conceptual clarity while reducing misconceptions. It highlights the importance of integrating extracted and stipulated definitions into teaching to improve student engagement and learning outcomes. Recommendations are provided to help educators enhance pedagogical practices in linear algebra, fostering deeper comprehension and application of abstract mathematical concepts.